Mapping the competency needs of the fashion industry and its relevance to the competencies of Diploma 4 fashion technology students at Yogyakarta State University - Fitri Nurjanah; Widihastuti Widihastuti (ARKA INSTITUTE, 2026)
Vocational higher education plays a strategic role in producing graduates whose competencies align with labor market demands. Nevertheless, discrepancies persist between the competencies of fashion graduates and the evolving requirements of the fashion industry due to shifting job roles and emerging skill demands. This study aims to map industry-required competencies, identify competencies possessed by D4 Fashion Technology students, and analyze the level of relevance between them. A mixed methods approach with a sequential explanatory design was employed. Quantitative data were collected through structured questionnaires distributed to division heads, managers, business owners in fashion companies, as well as students and alumni of the D4 Fashion Technology program at Universitas Negeri Yogyakarta. Qualitative data were obtained through semi-structured interviews and open-ended questionnaire responses. Data were analyzed using descriptive statistics and thematic coding. The findings reveal that 133 competency items are required by the industry with six additional competencies identified, while students possess 136 competency items with nine additional competencies. The overall relevance level reached 98%, categorized as highly relevant. These results indicate strong alignment between vocational education outcomes and industry needs, while underscoring the importance of continuous curriculum evaluation and development.